Financial statistics and mathematical finance : methods, models and applications - Steland, Ansgar (Chichester, West Sussex, United Kingdom : Wiley, 2012)
"The book will focus on elementary financial calculus, statistical models for financial data, option pricing.
Elementary financial calculus -- Arbitrage theory for the one-period model -- Financial models in discrete time -- Arbitrage theory for the multi-period model -- Brownian motion and related processes in continuous time -- Itō calculus -- The Black-Scholes model -- Limit theory for discrete-time processes -- Special Topics -- Appendix A -- Appendix B: Weak convergence and central limit theorems.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Business mathematics; Calculus; Business mathematics; Calculus; BUSINESS & ECONOMICS -- Econometrics; Business mathematics; Calculus; Business mathematics; Calculus; Electronic books; Electronic books